2012
DOI: 10.3389/fnhum.2012.00004
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Genetic Variation Promotes Human Trust Behavior

Abstract: Given that human trust behavior is heritable and intranasal administration of oxytocin enhances trust, the oxytocin receptor (OXTR) gene is an excellent candidate to investigate genetic contributions to individual variations in trust behavior. Although a single-nucleotide polymorphism involving an adenine (A)/guanine (G) transition (rs53576) has been associated with socio-emotional phenotypes, its link to trust behavior is unclear. We combined genotyping of healthy male students (n = 108) with the administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 46 publications
5
118
0
2
Order By: Relevance
“…More specifically, some findings indicate that carriers of the A allele (i.e., AA or AG) are, relative to G homozygotes, less empathic and more reactive to stress (Rodrigues, Saslow, Garcia, John, & Keltner, 2009), exhibit lower trust-related behaviors (Krueger et al, 2012), and prove to be less sensitive parents (Bakermans-Kranenburg & van Ijzendoorn, 2008;Klahr, Klump, & Burt, 2015). Moreover, at least one of two meta-analyses has documented associations between rs53576 and sociality (e.g., extraversion, social skills, and prosocial behavior).…”
Section: Oxytocin Receptor Genementioning
confidence: 99%
“…More specifically, some findings indicate that carriers of the A allele (i.e., AA or AG) are, relative to G homozygotes, less empathic and more reactive to stress (Rodrigues, Saslow, Garcia, John, & Keltner, 2009), exhibit lower trust-related behaviors (Krueger et al, 2012), and prove to be less sensitive parents (Bakermans-Kranenburg & van Ijzendoorn, 2008;Klahr, Klump, & Burt, 2015). Moreover, at least one of two meta-analyses has documented associations between rs53576 and sociality (e.g., extraversion, social skills, and prosocial behavior).…”
Section: Oxytocin Receptor Genementioning
confidence: 99%
“…For example, GG carriers displayed higher degrees of warm and empathic parenting than did carriers of the A allele (Bakermans-Kranenburg & van Ijzendoorn, 2008). Other studies also showed that individuals with one or two copies of the A allele exhibited lower levels of behavioral empathy and less positive affect (Rodrigues, Saslow, Garcia, John, & Keltner, 2009), and A allele carriers showed lower trust levels than did individuals with the G allele (Krueger et al, 2012). A recent preliminary study revealed associations between OXTR rs53576 and children's mind-reading abilities (Lucht et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research correlating the three possible alleles of the gene (GG, AG, AA) with different social behaviors are a reality that only the most dogmatic sociologists can ignore (see, for example, Rodrigues et al, 2009;SaphireBernstein et al, 2011;Tabak et al, 2013;Tost et al, 2010;Walum et al, 2012). One of them has already provided evidence that individuals with the GG allele show a more trusting behavior than the rest in a trust game (Krueger et al, 2012). While TOR has nothing to say about these biochemical processes that bias our perceptions and beliefs, EP offers an interpretative framework capable of integrating all these empirical results.…”
Section: How We Make Decisionsmentioning
confidence: 99%